2013
DOI: 10.1128/aac.01882-12
|View full text |Cite
|
Sign up to set email alerts
|

A Staphylococcus xylosus Isolate with a New mecC Allotype

Abstract: jRecently, a novel variant of mecA known as mecC (mecA LGA251 ) was identified in Staphylococcus aureus isolates from both humans and animals. In this study, we identified a Staphylococcus xylosus isolate that harbors a new allotype of the mecC gene, mecC1. Whole-genome sequencing revealed that mecC1 forms part of a class E mec complex (mecI-mecR1-mecC1-blaZ) located at the orfX locus as part of a likely staphylococcal cassette chromosome mec element (SCCmec) remnant, which also contains a number of other gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 32 publications
1
58
0
1
Order By: Relevance
“…This mecC gene has also been reported in CoNS as Staphylococcus stepanovicii, Staphylococcus xylosus and Staphylcoccus scirui (Harrison et al, 2013a(Harrison et al, , 2013bLoncaric et al, 2013). As already suggested for the mecA gene, we can probably infer that the origin of the mecC gene is also among the CoNS (Tsubakishita et al, 2010;Couto et al, 2013).…”
Section: Assessment Of Methicillin-resistant Coagulasenegative Staphysupporting
confidence: 70%
“…This mecC gene has also been reported in CoNS as Staphylococcus stepanovicii, Staphylococcus xylosus and Staphylcoccus scirui (Harrison et al, 2013a(Harrison et al, , 2013bLoncaric et al, 2013). As already suggested for the mecA gene, we can probably infer that the origin of the mecC gene is also among the CoNS (Tsubakishita et al, 2010;Couto et al, 2013).…”
Section: Assessment Of Methicillin-resistant Coagulasenegative Staphysupporting
confidence: 70%
“…The phylogenetic relationships of one representative of each type of ccr gene (19) and the mec gene complexes containing the blaZ gene (5)(6)(7)20) were investigated by the construction of a maximum likelihood phylogenetic tree using the SeaView program, version 4.4.0 (21), with nucleotide sequences deposited in the ENA/GenBank databases. Sequences were aligned using MUSCLE, and the trees were built with PhyML using a general time-reversible (GTR) model.…”
Section: Methodsmentioning
confidence: 99%
“…The mecA homologue mecC has a reported prevalence rate of 0.5% for MRSA and has recently been reported in coagulase-negative staphylococcus (5,11,15,23). It is characterized by an oxacillin-resistant/cefoxitin-sensitive profile with Vitek II in S. aureus and a negative mecA PCR (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown a close correlation between oxacillin resistance and the presence of the mecA gene (4,(8)(9)(10)(11)(12)(13)(14), changes in the epidemiology of resistance and the methodology of phenotypic tests necessitate ongoing appraisal of the role of routine sensitivity testing in the determination of beta-lactam resistance in coagulase-negative staphylococci.…”
mentioning
confidence: 99%